Case report: Suspecting guanine nucleotide-binding protein beta 1 mutation in dyskinetic cerebral palsy is important - Choi, Han-Byeol; Na, Yoonju; Lee, Jiwon; Lee, Jeehun; Jang, Ja-Hyun; Kim, Jong-Won; Kwon, Jeong-Yi (Frontiers in Pediatrics, 2023)
Herein, we describe the case of a 43-month-old girl who presented with clinical manifestations of dyskinetic cerebral palsy (CP), classified as the Gross Motor Function Classification System (GMFCS) V. The patient had no family history of neurological or perinatal disorders. Despite early rehabilitation, serial assessments using the Gross Motor Function Measure (GMFM) showed no significant improvements in gross motor function. Brain magnetic resonance imaging showed nonspecific findings that could not account for developmental delay or dystonia. Whole-genome sequencing identified a heterozygous NM_002074.5(GNB1):c.239T>C (p.Ile80Thr) mutation in guanine nucleotide-binding protein beta 1 (GNB1) gene. Considering this case and previous studies, genetic testing for the etiology of dyskinetic CP is recommended for children without relevant or with nonspecific brain lesions.